EFFECT OF 12.5% VIRGIN COCONUT OIL ON PORPHYROMONAS GINGIVALIS AND TREPONEMA DENTICOLA BACTERIAL COLONIZATION - Dewi, Ratna Sari; Gita, Farisza; Bahtiar, Boy; Kasim, Hocky Benny (International Journal of Applied Pharmaceutics, 2018)
Aim: The aim of this study was to analyze the clinical effect microbiological of pure coconut oil 12.5% on the decrease in a number of bacteria P. gingivalis and T. denticola on the margin of porcelain fused to metal crown. Methods: 23 subjects, were patients with porcelain fused to metal crown in posterior of Faculty of Dentisty Universitas Indonesia â€˜dental hospital. TheyÂ  fill the informed consent, clinical periodontal examination. Patients were gargled twice daily with a pure coconut oil 12.5% of 30cc for 1 min performed for 4 days. Sampling of saliva were collected with paper point for calculating the number of bacteria P. gingivalis and T. denticola using real-time polymerase chain reaction. Conclusion: Using Pure coconut oil 12.5% showed decrease amount of bacteria P. gingivalis and T. denticola in the margin porcelain fused to metal crown